A Pairwise Test Suite Generator based on Melody Search Algorithm - Toh, S. Yuen; Al-Omoush, Ala'a A.; Foo, W. Wen; Goh, G. Hau; Abdul, Rahman; Alsewari, Abdulrahman A. (Medwell Journals, 2016)
Melody Search Algorithm (MS) has been adopted to solve many optimization problems. This paper will introduce MS as a pairwise testing strategy called a Pairwise Test suite generator based MS (PTMS). A pairwise testing is an operative approach in the combinatorial test suite construction. It will reduce the construct test suite size to save the testing time with effective defects detecting. The proposed strategy generate the test suite with real-value variables. A comparative evaluation shows the PTMS efficient in constructing a minimum test suite.